Quick Reduce: Dark Energy Survey Camera mountain-top Quality Assessment tool and its master calibration pipeline - Fausti Neto, Angelo; Costa, Luiz da; Ogando, Ricardo; Egeland, Patricia; Maia, Marcio; Peloso, Eduardo del; Singulani, Cristiano; Machado, Valter; Souza, Carlos Adean de (Anais do Brazilian e-Science Workshop (BreSci), 2013)
To uncover the misteries of dark energy the Dark Energy Survey is covering 5,000 square degrees of the southern hemisphere with a 500 Mpixel camera. In order to timely assess the quality of data on mountain-top, a system was devised to process these huge frames, extract information and keep them in a database, providing a friendly interface for the observer to interact with. This work describes the challenges involved in the parallelization of field-of-views, their 62 chips, avoiding IO and memory trouble in the restricted computational mountain-top environment and at the same time delivering nearly science grade data to observers.